Primary angiosarcoma of the testis: report of a rare entity and review of the literature - Rao Uma NM; Armah Henry B; Parwani Anil V (BMC, 2007)
Abstract Background Primary testicular angiosarcomas are extremely rare, and their clinicopathologic features are not well described. Our objective was to further define the clinical features and pathologic spectra of primary testicular angiosarcomas. Methods Six previously reported case reports were identified in the English language medical literature using MEDLINE and a subsequent bibliographic search of all pertinent reports and reviews was performed. After excluding 2 cases because they did not involve the testis, we identified 4 previously reported cases of true primary testicular angiosarcoma. We also searched the electronic medical archival records of our institution and identified one additional unreported case of true primary testicular angiosarcomas. Data were extracted on the demographics, predisposing factors, clinical presentation, gross pathology, microscopic pathology, immunophenotype, therapy, and outcomes of each of these 5 cases of true primary testicular angiosarcomas. Results Primary testicular angiosarcomas were found at a mean age of 43.4 years. None of the cases was associated with exposure to radiation, arsenic, thorium dioxide, or vinyl chloride. However, 1 case was associated with hydrocele. It typically presented with painless mass (mean size, 6.3 cm). Histologically, all showed classic anastomosing channels lined by plump hyperchromatic cells, though most showed epithelioid cytology and some showed solid architectural pattern. One patient had multiple metastatic recurrences but eventual outcome was not available, and 1 patient died a month after diagnosis from stroke but no autopsy was performed. The remaining 3 patients were alive at the time of publication of their respective cases (mean, 17 months). Conclusion Primary testicular angiosarcomas are typically rare tumors of men of all ages that appear to segregate into 2 groups; one associated with teratoma and occurring in young people, and the other occurring in the elderly and not associated with germ cell neoplasm, but may be associated with chronic hydrocele. They present with advanced disease and show a wide histologic spectrum. However, their prognosis may be better than previously thought.